Efektivitas Sosial Media Sebagai Media Promosi Desa Surabaya Timur - Mardian Herri Pratama Mardian; Desy Misnawati; Muhammad Renaldi (Yayasan Literasi Sains Indonesia, 2022)
Various types of social media have now become public consumption. Social media is not only used for entertainment, but is a place and use it in business. Promotion is one part of doing business on social media. With a wide reach throughout the world, it doesn't take long for consumers to get the information they want. The purpose of this research is to see the effectiveness of social media as a promotion media for East Surabaya Village, Kec. Supreme Court Appeal of South OKU Prov. South Sumatra. The results of the study show that social media is quite effective in marketing a product, but with the algorithms owned by each social media application, account management must be optimized.